A CONTENT ANALYSIS OF THE SOUTH AFRICAN NATIONAL DRUG MASTER PLAN: LESSONS FOR ALIGNING POLICY WITH SOCIAL DEVELOPMENT - Geyer, Stephan; Lombard, Antoinette (Social Work/Maatskaplike Werk, 2014)
If drug policies, such as the South African National Drug Master Plan 2006-2011 (NDMP2), are drafted according to a social developmental perspective, the efforts of stakeholders could be strengthened to mitigate substance abuse, eradicate drug-related crimes, and contribute towards achieving social development goals. This study determined whether the NDMP2 is drafted in accordance with a social development perspective. Quantitative research, with content analysis as research strategy, was adopted to determine whether indicators of social development are embedded in the manifest content of the NDMP2. Results show the NDMP2 has both strengths and limitations when interpreted from a social development perspective.